PERMA1NAN TROMPET OLEH WYNTON MARSALIS DALAM KONSERTO DALAM ES MAYOR HOB VII E:1 KARYAYOSEPH HAYDN: SUATU KAJIAN ANALISIS INTERPRETASI - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2002)
ABSTRACT Malinowsky has developed the theory of culture's element that is so complicated. One of these elements initially related to the human need to satisfy their instinct desire to the sense of beauty. The artist turns the art-form of a composer to a life performance through his technical playing and interpretation of the genre. In this sense, the interpretation is the most expressive meaning toward his or her optimum quality of performance. This study focuses on how one of the world's most talented artists like Wynton Marsalis interpret the composition through his musicianship and contemporary approach of the genre. This will be analized with the help of the musicology, aesthetics and philosophical approaches. The idea is to study the interpretation to composer's art-form by contemporary young artist of world's class. Some of the elements to be studied are the dynamic interpretation, the tempo and the phrasering techniques. These are to be divided in three chapters that are constructive, expressive and aesthetics. It is also important to know the biographical background of the artist